Pengaruh Early Warning System Dan Risk Based Capital Terhadap Tingkat Kesehatan Keuangan Perusahaan Asuransi - Setianingsih, Novie Astuti; A, Wiwiek Kusumaning; Sari, Hanifah Puspita (Owner : Riset dan Jurnal Akuntansi, 2024)
Insurance is an agreement between two parties, namely the insurance company and the policyholder, which forms the basis for receiving premiums by the insurance company in return. In determining insurance, the public needs an early warning system and risk-based capital analysis to determine the financial health of insurance companies, so that they can provide maximum protection to investors. This study aims to determine and analyze the level of financial soundness of insurance companies listed on the Indonesia Stock Exchange. The issuers selected are issuers from insurance companies listed on the IDX in 2019-2022. Determination of the sample using purposive sampling method, namely determining the sample from the existing population based on criteria. Data obtained from the Indonesian Capital Market Directory (ICMD). This research uses multiple linear regression analysis with SPSS application. The results of research on the Solvency Margin Ratio, Underwiting Ratio, Loss Ratio, Investment Returns Ratio, Liability to Liquid Ratio and Net Premium Growth Ratio contained in the Early Warning System and Risk Based Capital have a significant and positive effect on the level of company health, especially for insurance companies.